PERAN MOTIVASI KERJA SEBAGAI MEDIASI PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI (Pada Dinas Perdagangan dan Perindustrian Kabupaten Jombang) - Astutik, Mardi; Ati, Novia Laras; Sandy, Widy Taurus (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine, analyze, and explain the influence of Transformational Leadership Style and Work Motivation on Employee Performance, Transformational Leadership Style on Work Motivation, and the mediating role of Work Motivation in the influence of Transformational Leadership Style on Employee Performance. Sample of 47 employees at the Department of Trade and Industry of Jombang Regency. Research data was obtained from distributing questionnaires using a Likert scale. The data analysis technique uses SEM-PLS (Structural Equation Modeling Partial Least Square) with the help of the SmartPLS application. The results of this study indicate that Transformational Leadership Style can increase employee performance, Transformational Leadership Style can increase work motivation, work motivation can increase employee performance, and work motivation can partially mediate the relationship between Transformational Leadership Style and Employee Performance